Multi-polar scripts: Techno-regulatory environments and the rise of precision oncology diagnostic tests. (July 2022) - Cambrosio, Alberto; Campbell, Jonah; Keating, Peter; Bourret, Pascale
Abstract: The paper examines the development and marketing of five multi-gene tests, a.k.a. as tumor signatures, designed to aid clinicians and cancer patients in therapeutic decision-making, and, in particular, to avoid overtreatment. We build on a 2011 paper that investigated the emergence of this new domain by opening the 'black box' of two pioneering tests and analyzing the hybrid, scientific-regulatory 'scripts' that were built into them. In subsequent years, second-generation tests, produced by a diverse blend of academic and commercial initiatives, have become available, and they all built into their scripts the lessons learned from their predecessors. The present paper confirms the heuristic value of the initial script-analysis but expands it to consider the multi-polar nature of the space within which multigene tests mutually position themselves. We examine how the tests were first problematized — i.e. how they described and prescribed the kind of world in which they would operate — and how their initial problematization was re-specified following the emergence of a comparative arena and their resulting informational enrichment. In parallel, we explore valuation processes, i.e. the evolving definition of the set of referents against which the assays are mutually compared, and the debates about the appropriate criteria for doing so. We note that the cancer diagnostic industry is involved in the reconfiguration of the multi-polar environment defined by socio-technical, techno-scientific, and regulatory matters of concern that seamlessly blend commercial and scientific considerations. Highlights: Breast cancer multi-gene tests embed scientific-regulatory scripts. Scripts describe and prescribe the world in which tests should operate. Valuation processes define the evolving criteria for test comparison. Regulation is an endogenous component of valuation processes. Test development seamlessly blends commercial and scientific considerations.